Politik, Kekuasaan, dan Kekerasan Perspektif Hannah Arendt - Stanislaus Nugroho (Respons: Jurnal Etika Sosial, 2009)
Abstract: Politics is not a simple word. Aristotle identifies it with human togetherness. In line with this identification, Hannah Arendt suggests that politics is not a kind of dominating actions, but the way in which the human beings promote freedom of actions in the public sector. The essence of politics, then, is communication. In this line of thought, power can be understood as one’s ability to act/behave with and within others/in togetherness with others on base of a given mandate. Violence is nothing else but an anti-political stance of togetherness.Kata Kunci: Politik, kekuasaan, kekerasan, kebebasan, komunikasi